Four-Year and Five-Developing-Stage Dynamic QTL Mapping for Tiller Number in the Hybrid Population of Agropyron Gaertn. - Che, Yonghe; He, Yutong; Song, Nan; Yang, Yanping; Wei, Lai; Yang, Xinming; Zhang, Yan; Zhang, Jinpeng; Han, Haiming; Li, Xiuquan; Zhou, Shenghui; Liu, Weihua; et al. (Frontiers in Plant Science, 2022)
Tiller number (TN) is an important agronomic trait affecting gramineous crop yield. To understand the static and dynamic information of quantitative trait locus (QTLs) controlling TN of Agropyron Gaertn., both the unconditional and conditional quantitative trait loci (QTL) mapping of TN were conducted using a cross-pollinated (CP) hybrid population with a total of 113 plant lines from the cross between Agropyron cristatum (L.) Gaertn. Z1842 and Allium mongolicum Keng Z2098, based on the phenotypic data of TN at five developmental stages [i.e., recovering stage (RS), jointing stage (JS), heading stage (HS), flowering stage (FS), and maturity stage (MS)] in 4 years (i.e., 2017, 2018, 2020, and 2021) and the genetic map constructed of 1,023 single-nucleotide polymorphism (SNP) markers. Thirty-seven QTLs controlling TN were detected using two analysis methods in 4 years, which were distributed in six linkage groups. Each QTL explained 2.96–31.11% of the phenotypic variation, with a logarithum of odds (LOD) value of 2.51–13.95. Nine of these loci detected both unconditional and conditional QTLs. Twelve unconditional major QTLs and sixteen conditional major QTLs were detected. Three relatively major stable conditional QTLs, namely, cQTN1-3, cQTN1-5, and cQTN4-1, were expressed in 2020 and 2021. Meantime, two pairs of major QTLs cQTN1-5 and qTN1-4 and also cQTN2-4 and qTN2-3 were located at the same interval but in different years. Except for qTN2-2 and qTN3-5/cQTN3-5, other thirty-four QTLs were first detected in this study. This study provides a better interpretation of genetic factors that selectively control tiller at different developmental stages and a reference for molecular marker-assisted selection in the related plant improvement.